Impacts of crime attractors and generators on criminality in Montreal - Demeau, Elodie (Canadian journal of criminology and criminal justice, 2018)
Urban institutions and facilities modulate criminal opportunities by influencing the number and type of people using them. Based on this finding, the present study attempts to assess the effect of several types of facilities, generally identified in the literature as attractors and generators of crime, on assault, theft, robbery, and motor vehicle theft in Montreal. To this end, the number of crimes and different facilities, as well as several socio-demographic indicators, were measured for the 3,195 dissemination areas. Except for laundromats and pawnshops, all the facilities assessed have a significant effect on one or more types of crime. The results obtained, which differ from the results for other North American cities, reject the generalization of such studies in other cities. While these differences could be attributed to dissimilarities at the urban or sociocultural level, it is also plausible that the methodological choices made can be the source of these differences. Limitations and future directions are discussed.